RP-HPLC-PDA Method for Simultaneous Quantification of Montelukast, Acebrophylline and Desloratadine Tablets - Mamatha, J.; Devanna, N. (Asian Journal of Chemistry, 2018)
A simple, fast, accurate and specific RP-HPLC-PDA method has been developed for the simultaneous quantification of montelukast, acebrophylline and desloratadine in bulk and tablet dosage form. The chromatographic separation was performed on a reverse phase BDS C8 Column (150 × 4.6mm, 5 μm particle size) consisting mobile phase of potassium hydrogen ortho-phosphate buffer:acetonitrile (40:60 v/v), with a flow rate 1 mL/min, temperature 30 ºC and UV detection wavelength 280 nm. The retention times of montelukast, acebrophylline and desloratadine were observed as 2.04, 2.68 and 3.77 min, respectively. The developed method was validated by validation parameters such as linearity, range, accuracy, precision and robustness. The results obtained for validation parameters are within the limits as per ICH guidelines. The linearity of the drugs were obtained in the range of 5-30 ppm for montelukast, 100-600 ppm acebrophylline and 2.5-15 ppm for desloratadine. % RSD from precision studies were 0.4, 0.1 and 1.0 mean percentage recovery from accuracy studies were found to be 98.47, 98.71 and 100.11 for montelukast, acebrophylline and desloratadine respeactively. Limit of detection values were found as 0.01, 0.32 and 0.01 for montelukast, acebrophylline and desloratadine, respectively. Limit of quantification values were found as 0.03, 0.98 and 0.04 montelukast, acebrophylline and desloratadine, respectively. The method designed and validated can be successfully used for the regular quantification of montelukast, acebrophylline and desloratadine in tablet and bulk forms.